2015
DOI: 10.1007/s00345-015-1530-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three-dimensional printing for laparoscopic partial nephrectomy of renal tumors: a preliminary report

Abstract: Generating kidney models of T1N0M0 tumors with 3D printing are feasible with refinements to be performed. Face and content validity was obtained when those models were presented to experienced urologists for making practical planning and training. Understandings of the disease and procedure from patients were well appreciated with this novel technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 13 publications
3
95
0
2
Order By: Relevance
“…Comparison of dimensional accuracy or renal tumour volume between 3D printed models and original imaging data/or surgical results was reported in 5 studies (18,24,(32)(33)(34). Results of these studies showed that 3D printed models are highly accurate in replicating anatomical structures or detecting tumour volumes with mean difference <10% in dimensional measurements between 3D printed models and original imaging data or surgically resected specimens ( Table 1).…”
Section: Quantitative Assessment Of 3d Printed Kidney Modelsmentioning
confidence: 90%
See 3 more Smart Citations
“…Comparison of dimensional accuracy or renal tumour volume between 3D printed models and original imaging data/or surgical results was reported in 5 studies (18,24,(32)(33)(34). Results of these studies showed that 3D printed models are highly accurate in replicating anatomical structures or detecting tumour volumes with mean difference <10% in dimensional measurements between 3D printed models and original imaging data or surgically resected specimens ( Table 1).…”
Section: Quantitative Assessment Of 3d Printed Kidney Modelsmentioning
confidence: 90%
“…Of 15 studies, 8 (53%) provided quantitative assessments of 3D printed kidney models with reported applications (16,18,24,29,30,(32)(33)(34). Comparison of dimensional accuracy or renal tumour volume between 3D printed models and original imaging data/or surgical results was reported in 5 studies (18,24,(32)(33)(34).…”
Section: Quantitative Assessment Of 3d Printed Kidney Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…These 3-D models can also be used for patient education preoperatively in terms of estimating the amount of functional renal parenchyma that will remain after resection and setting expectations regarding outcomes and success of RAPN [38]. 3-D printing technology has also gained popularity in creating renal tumor models and has been successfully used for preoperative surgical planning and patient education [39].…”
Section: -D Imagingmentioning
confidence: 99%